2000
DOI: 10.1111/j.1755-6686.2000.tb00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Provision of dietary advice in selected centres across Europe

Abstract: summary The EDTNA/ERCA survey of the provision of dietary advice in renal care was the second project organised through the Collaborative Research Programme (CRP). Data was collected from 51 participating centres in 19 countries. Advice on nutrition was provided by a multidisciplinary team, normally led by a specialist renal dietitian or a medical doctor, in 90% of participating centres. There was a general consensus on the type of advice that should be provided, in that most patients routinely received advice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Another survey, performed by the EDTNA/ERCA's collaborative research programme, demonstrated that there were differences in the provision of dietary advice by renal care professionals across Europe (Nevett et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Another survey, performed by the EDTNA/ERCA's collaborative research programme, demonstrated that there were differences in the provision of dietary advice by renal care professionals across Europe (Nevett et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…There was a general consensus on the type of advice that should be provided; for example, in over 70% of centres patients received advice routinely on the intake of protein, energy and minerals. There was also agreement on daily protein requirements, and that they should be expressed as g/kg, but there was considerable variation in the way that body weight was calculated to determine the dietary intake for an individual patient (Nevett et al, 2000).…”
Section: Provision Of Dietary Advicementioning
confidence: 99%